2017
DOI: 10.2134/itsrj2016.10.0837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Occurrence of Turfgrasses and Weeds after Repeated Overseeding on Fairways

Abstract: Research concerning the cultural practice of golf course fairways is important because legislation on pesticide reduction in Europe and North America may potentially cause serious weed problems. Establishing a strong, competitive turfgrass sward may aid in reducing the invasion of broadleaved weeds and Poa annua L. The objective of this research was to determine changes in the grass species composition and weed occurrence of in‐use fairway turfs after repeated overseeding of three grass species separately: Lol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Proper species selection for overseeding purposes is also crucial. Perennial ryegrass showed good germination rates regardless of whether or not water and fertilizer were applied (Dahl‐Jensen, Bühler, Kvalbein, & Aamlid, 2017; Elford, Tardif, Robinson, & Lyons, 2008). Additionally, perennial ryegrass germinates quickly and has good root and shoot competition against weeds (Haugland & Froud‐Williams, 1999).…”
Section: Seeding and Overseeding Strategiesmentioning
confidence: 99%
“…Proper species selection for overseeding purposes is also crucial. Perennial ryegrass showed good germination rates regardless of whether or not water and fertilizer were applied (Dahl‐Jensen, Bühler, Kvalbein, & Aamlid, 2017; Elford, Tardif, Robinson, & Lyons, 2008). Additionally, perennial ryegrass germinates quickly and has good root and shoot competition against weeds (Haugland & Froud‐Williams, 1999).…”
Section: Seeding and Overseeding Strategiesmentioning
confidence: 99%
“…acid) (Marth and Mitchell 1944), herbicides have become the main tool used by managers to control weeds in turfgrass (Dahl Jensen et al 2017;Hatcher and Froud-Williams ;Heap 2014;McElroy and Martins 2013).…”
mentioning
confidence: 99%
“…More than a decade of trials in Europe and North America have shown that overseeding can be an effective weed suppression strategy. Overseeding with Lolium perenne L. (perennial ryegrass) has been found to be effective for increasing turfgrass cover and, in some instances, decreasing weed pressure (Dahl Jensen et al, 2017;Miller and Henderson, 2012), especially for outcompeting Poa annua L. (annual bluegrass) (Aamlid et al, 2012). Overseeding ranges in effectiveness depending on the application frequency, rate, location, and climate conditions (Aamlid et al, HORTSCIENCE • https://doi.org/10.21273/HORTSCI15419-20 2012; Elford et al, 2008;Larsen et al, 2004).…”
mentioning
confidence: 99%